Larval development of the fiddler shrimp, Metapenaeopsis stridulans (Alcock, 1905) (Decapoda: Penaeidae) reared in the laboratory - Chong, V.C.; Sasekumar, A. (Taylor & Francis, 1994)
Larvae of Metapenaeopsis stridulans (Alcock, 1905) from Malaysia were successfully reared in the laboratory from the egg to the 1st post-larval stage. The larvae developed through six naupliar, three protozoeal and four mysis stages. The morphology of all these larval stages is described and figured.